THE EFFECT OF AGE ON THE PERFORMANCE OF MEMBERS OF THE PARLIAMENT OF THE KURDISTAN REGION OF IRAQ, 1992-2022 - Sadoon, Hajar; Abdulrahman, Mohammed (Humanities Journal of University of Zakho, 2024)
The biological age of Human beings influences the activities and tasks assigned to each person. Additionally, age plays a significant role in the performance of parliaments. Within this framework, the age of parliamentarians is closely linked with parliamentary performance in multiple ways; experience and skills, true representation, knowledge, and physical and technical abilities. Most parliaments in democratic societies have two primary functions: legislation and oversight, and the age of parliamentarians directly impacts the fulfillment of these two functions. Parliament is one of the most important institutions in the political system of any democratic state. Therefore, it is essential to identify which age group is the most effective and efficient to perform the tasks assigned to members of the parliament.This research focuses on the five parliamentary terms of the Iraqi Kurdistan parliament from 1992 when the first election took place until 2022. During this period, five elections have been conducted in the Kurdistan Region of Iraq. Moreover, all three aforementioned age groups have been elected in a variety of numbers in those parliamentary terms. By examining the composition of all five terms of the Iraqi Kurdistan parliament in terms of the age group of parliamentarians, this research aims to identify which age group is the most active and efficient in terms of execution of essential parliamentary functions. By comparing data from all five parliamentary terms of the Iraqi Kurdistan parliament with a special focus on the fifth parliamentary term elected in 2018, this research hypothesizes that the Middle Age group of parliamentarians has been the most effective and efficient in the parliament of the Iraqi Kurdistan Region throughout its existence.